A simple and cheap 3d reconstruction system of embryonic structures from serial sections (2007)
This work explaines how to setup and use a very cheap and simple 3D reconstruction system, for embryonic structures, using as an example the innervation of E19 hindlimb rat embryo. It also shows how results of good level can be achieved, such as, form, location and distribution of the structures of interest, obtaining additionally quantitative data of the size (volume and superficial area), and form. All the results mentioned above were obtained from the operation of free software available at the Internet.